1980
DOI: 10.1007/bf00505739
|View full text |Cite
|
Sign up to set email alerts
|

Effects of mild hyperkalemia on conduction velocity and effective refractory period in various parts of the dog heart in situ

Abstract: Effects of mild hyperkalemia on conduction velocity, effective refractory periods (ERPs) and sinus rate were studied on 16 anesthetized dogs, using endocavitary His bundle recordings, the extrastimulus method and standard electrocardiogram. Six dogs were placed under acetylcholine infusion (300 micrograms/kg/min) (ACh group), 10 received atropine sulfate 0.2 mg/kg intravenously (atropine group). Intraventricular conduction time, ventricular ERP and QRS duration of the EKG were studied on 7 other open-chested d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1982
1982
2005
2005

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…Experimental studies are limited, but those available have not shown an effect of acetylcholine on conduction velocity (20,31).…”
Section: Comparison Of Dynamic Changes In the Electrophysiological Prmentioning
confidence: 99%
“…Experimental studies are limited, but those available have not shown an effect of acetylcholine on conduction velocity (20,31).…”
Section: Comparison Of Dynamic Changes In the Electrophysiological Prmentioning
confidence: 99%